Romani Families Transforming the School - Xavier Folch (Networks: An Online Journal for Teacher Research, 2004)
When we explain to people that we are lucky enough to work in neighborhoods with schools where a large number of families are Romany, at first they do not understand why we say this. When we tell people everything that we do, they do not believe it is possible. Because of the stigmatization of Roma there are labels associated to them, which lead to presumptions that those who relate to or work with Roma, rather than being lucky are unfortunate. It surprises people, however, that all those who work with Roma in a respectful way, avoiding stereotypes and clichés, learn to value all the positive aspects of the Romani culture.